PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN PENGUSAHA KENA PAJAK DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA BANDAR LAMPUNG - Maria, Delli (Jurnal Bisnis Darmajaya, 2015)
This study aims to prove the effect of the modernizing tax administration system with the level of compliance of employersÂ  Tax Service Office ( KPP ) Primary area of ââBandar Lampung . The study was conducted at the Tax Service Office ( KPP ) Primary area in Bandar Lampung , Teluk Betung , Tanjung Karang andÂ  Kedaton. The method used in this research is descriptive qualitative method and verification approach . Questionnaires distributed to the Taxable Person ( PKP ) are listed in the Tax Service Office ( KPP ) Primary area in Bandar Lampung . Hypothesis testing techniques performed using the t test . The results show the implementation of the modernization of the tax administration system in Tax Service Office (KPP) in Bandar Lampung significant effect on the level of compliance Taxable Person with the positive direction of the relationship . This suggests that the higher the modernization of the tax administration system provided by the Tax Service Office ( KPP ) and will increase compliance Taxable Person ( PKP ) in paying the taxesKeywords : Systems Administration Modernization , Tax Taxable , Tax Compliance